Prevalence of undernutrition and risk factors of severe undernutrition among children admitted to Bugando Medical Centre in Mwanza, Tanzania. Issue 1 (December 2016) - Ahmed, Maimuna; Hokororo, Adolfine; Kidenya, Benson; Kabyemera, Rogatus; Kamugisha, Erasmus
Abstract Background Malnutrition is a major public health problem in developing countries including Tanzania, contributing up to 50 % of under-five mortality. East Africa region was among the three United Nations (UN) subregions with the highest prevalence of stunting in 2011. In resource limited countries, the available little resources in hospitals are likely to be used focusing the primary clinical problem that led to admission of children leaving moderate and mild malnutrion unattended. This work was conducted to determine the prevalence of under-nutrition and risk factors associated with severe malnutrition among undernourished children aged 6–60 months admitted to Bugando Medical Centre (BMC) paediatric wards. Method This was a hospital-based cross sectional study where by 720 children were screened in order to determine their nutritional status. Data were collected through measurement of weight/length or height, mid upper arm circumference (MUAC) and interpretation was done using Z-score (mild malnutrition ≤1SD, moderate malnutrition ≤2SD and severe malnutrition ≤3SD). The socio-demographic data were obtained using a questionnaire that was completed by interviewing children's parents/caregiver. Results Out of 720 screened children, 402 (55.8 %) were undernourished. Severe malnutrition was found in 178 (24.7 %) children and among these 97 (54.5 %) had marasmus. Risk factors associated with severe malnutrition were children with age less than 2 years, lack of vaccination, taking unbalanced diet, low maternal education and single parent, withp -value (<0.001, < 0.001, <0.001, 0.02, < 0.001) respectively. Conclusion This study show a high prevalence of malnutrition in hospitalized children and the majority was marasmic. The risk factors associated with severe malnutrition were described. We recommend improving the screening for undernutrition in all admitted patients so that proper management of this problem can be done concurrently with the primary clinical disease that led to admission.